Clinical features of medullary thyroid carcinoma and multiple - Gryczyńska, Maria (Contemporary Oncology/Współczesna Onkologia, 2005)
Medullary thyroid cancer (MTC) arises from C cells of the thyroid and accounts for 5-10% of all thyroid cancers. MTC can be sporadic (approximately 75%) or hereditary (approximately 25%) with an autosomal dominant pattern of transmission, as familial MTC (FMTC) or as part of a multiple endocrine neoplasia (MEN) type 2A or 2B. FMTC is characterized by the absence of other endocrinopathies or neural abnormalities in any affected family member. FMTC occurs late in the life, during the fourth-sixth decade. MEN 2A syndrome includes MCT, pheochromocytoma, and hyperparathyroidism with the incidence of clinical MTC during the second or third decade of life. MEN 2B syndrome is characterized by MTC, pheochromocytoma multiple mucosa neuromas, and marfanoid habitus with MTC occurs earlier and is more aggressive. MTCs produce calcitonin, the measurement of which can indicate the presence of tumors in people who are at risk and the effectiveness of therapy in treated patients. Mutations in the RET gene are critical for MTC pathogenesis and essential for the diagnosis of hereditary MTC. Surgical cure is possible in young patients with MEN 2 who undergo preventive thyroidectomy and in some patients with recurrent nodal metastatic disease in the neck. After total thyroidectomy, thyroxine treatment is given to maintain serum TSH within the normal range. There is no effective systemic therapy for MTC, and the role of radiotherapy is not well defined.